Hurtful authenticity or flattering lies / Nor Asni Syahriza Abu Hassan - Abu Hassan, Nor Asni Syahriza (Universiti Teknologi MARA, Kedah, 2023)
The Academy of Language Studies, Universiti Teknologi MARA (UiTM) Kedah branch is proud to present the first issue of its e-magazine, The Epitome, as our focus to highlight our commitment to contribute to the areas of creative writing. The Epitome aims to provide a platform for writers, educators, academicians, poet, and researchers to share their ideas, findings, knowledge, and experience, particularly on various creative writing genres - personal essays, poetry, short stories, songs, movie scripts, plays, and innovative projects in four different languages ( English, Bahasa Melayu, Mandarin, and Arabic).